Employee engagement, organisational commitment, and job satisfaction in Namibia, South Africa, and Zimbabwe: An exploratory study. Issue 4 (4th July 2019) - Maleka, Molefe; Mpofu, Mthokozisi; Hlatywayo, Clifford Kendrick; Meyer, Ines; Carr, Stuart; Parker, Jane
Abstract : The goal of this study was to measure employee engagement (EE), organisational commitment (OC), and job satisfaction (JS) in Namibia, South Africa, and Zimbabwe. We surveyed a convenience sample of 631 employees (South Africa: n = 219; Namibia: n = 212; and Zimbabwe: n = 200). The employees completed a selection of items from the Employee Engagement Scale, the Organisational Commitment Scale, and the Job Satisfaction Scale. Following analysis of variance and t -tests, results t -tests showed between-country differences in EE, OC, and JS in which South African employees reported higher scores than those from Namibia and Zimbabwe. Macro-level economic factors may explain the country differences in EE, OC, and JS.